Reflection and transmission of P-wave incident obliquely at the interface between an elastic solid and a fluid-saturated porous medium: a comprehensive study via the model of soil mechanics - Qiu, Lijun; Zhang, Bo (Frontiers in Physics, 2025)
IntroductionA model of soil mechanics is used to study the problem of reflection and transmission of an obliquely incident plane P-waveon a discontinuous interface. Based on the propagation theory of elastic waves in an elastic solid and a fluid-saturated porous medium, the propagation analysis model of P-wave incident obliquely at the interface of such media is established.MethodsThe theoretical formulas of reflection coefficients of P- and SV-waves and the transmission coefficients of P1-, P2-, and SV-waves are obtained in terms of the boundary conditions of the interface between an elastic solid and a saturated two-phase medium. Furthermore, the derived formulas in this paper are reduced to the reflection and transmission problems of P-wave incident on two different single-phase media to verify their correctness. Finally, numerical investigations are carried out on the variations of the reflection and transmission coefficients with the incident angle for various boundary conditions, wave frequency, and material characteristics (i.e., dynamic permeability coefficient, porosity, and Poisson’s ratio).ResultsIt is shown that the effects of incident angles, boundary conditions, wave frequency, and material characteristics on the reflection and transmission coefficients cannot be ignored.DiscussionThese conclusions are of guiding significancefor theoretical research of soil dynamics and engineering seismic exploration.